DINAMIKA PERILAKU POLITIK MASYARAKAT MENJELANG PEMILIHAN KEPALA DAERAH SERENTAK 2024 DI KECAMATAN LAWA KABUPATEN MUNA BARAT - Iriyani Astuti Arief; Muhammad Ishak Syahadat; M. Najib Husain (Halu Oleo University, 2023)
This research reviews the dynamics of the political behaviour of the people of Lawa District in the 2024 West Muna Regency regional head election, with a focus on Latugho Village, Lalemba Village, Wamelai Village, and Lapadaku Village. Through the concept of political behaviour, this research explores socio-political factors that influence political participation, especially the phenomenon of high abstention. Data was collected through questionnaires, literature studies, and documentation, and analyzed in three stages: data reduction, data presentation, and drawing conclusions. The research results show that the dynamics of political behavior are influenced by sociological, psychological and rational choice factors. Ethnicity is not dominant, while psychological factors (family) dominate with 27.5% influence. Rational choices, especially the vision and mission of the Regent candidate, influence 22.5% of the community. In conclusion, psychological factors are key in shaping political behaviour in Lawa District, where the family has a significant influence in political decision-making.